Cyclic behavior of self-tapping screwed laminated bamboo lumber connections subjected to cycle loadings - Chen, Chen; Ye, Zhangning; Yu, Xiaohong; Tor, Onder; Zhang, Jilei (BioResources, 2019)
Self-tapping screws are commonly used to connect critical structural components, such as legs to rails in chair construction, using laminated bamboo lumber (LBL) materials. The loosening of a connection is commonly seen in self-tapping screwed LBL connections before actual breakage of connections happens. The loosening of connections, especially those associated with chair legs, can significantly affect chair stability. Current furniture performance test standards have not address this issue, i.e., the minor loosening of a connection is not treated as a failure in the current standard because of the lack of better understanding the load-rotation-time behavior of various connections subjected to the cyclical loads. The effects of cyclic loading magnitude and orientation on the load-rotation-time behavior of L-shaped, end-to-side, single self-tapping screwed LBL connections were investigated. Results indicated that the Burger and Kelvin models could be used to describe the cyclic and recovery behavior of studied connections. Increasing the cyclic loading magnitude resulted in a decreasing trend for all viscoelastic constants. The most significant decrease in all viscoelastic constants occurred when the cyclic loading magnitude applied to connections increased from 50 to 60% of its corresponding ultimate static resistance loads.